KOMUNIKASI DELIBERATIF DAN FRAGMENTASI POSTMODERN: PERSPEKTIF FILSAFAT ILMU HABERMAS–LYOTARD PADA KASUS KERACUNAN MBG DI SEKOLAH - Reni Dian Anggraini (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2026)
This study examines deliberative communication and postmodern fragmentation in the MBG poisoning case in schools through the perspective of the Habermas-Lyotard philosophy of science. The background of this study is the strengthening crisis of public trust in the MBG program after the emergence of various poisoning incidents that gave rise to a narrative battle between the government, media, victims, and society. This study aims, first, to analyze the construction of the MBG poisoning discourse in Indonesia's digital public space. Second, to explain the failure of deliberative communication in the crisis through the perspective of Habermas. And third, to describe the fragmentation of narratives in the MBG debate through the perspective of Lyotard. The method used is a literature study with a critical discourse analysis approach. Data were analyzed through thematic coding of official government narratives, critical public narratives, and digital media responses to identify patterns of knowledge legitimacy and power relations in the MBG discourse. The results show that the MBG poisoning discourse in the digital public space shows tension between official truth claims and the empirical experiences of victims. From Habermas's perspective, the failure of deliberative communication is caused by the dominance of instrumental rationality that excludes equal, transparent, and rational public participation. From Lyotard's perspective, the MBG debate demonstrates the collapse of a single narrative and the emergence of a plurality of competing sub-narratives, thus fragmenting policy legitimacy. This study concludes that restoring the legitimacy of knowledge in MBG policy can only be achieved through deliberative, inclusive, and accountable public communication, accompanied by recognition of the diversity of community experiences and narratives.